Feasibility study of silica bead thermoluminescence detectors (TLDs) in an external radiotherapy dosimetry audit programme. (December 2017) - Jafari, S.M.; Distefano, G.; Lee, J.; Gouldstone, C.; Mayles, H.; Jupp, T.; Nisbet, A.; Clark, C.H.
Abstract: Purpose: Investigating the feasibility of using low-cost commercially available silica beads as novel thermo-luminescence dosimeters (TLD) for postal dosimetry audit. Methods: A mail-based dosimetry audit was designed to assess the positional and dosimetric accuracy of SABR-lung treatment delivery using alanine and EBT3-film, placed in a CIRS-anthropomorphic thorax phantom. In conjunction, the silica beads were dosimetrically characterised as TLDs and cross-calibrated against the alanine. A CT-scan of the phantom with pre-delineated volumes was sent to 20 RT centres and used to create a SABR plan using local current protocols and techniques. The silica beads were held in an insert, designed to match that of the alanine holder and ionisation chamber to give the same measurement length. The doses determined by the silica beads were compared to those measured by alanine, the local ionisation chamber, film and the TPS calculation. Results: The mean percentage difference between the doses measured by the silica beads and the calculated doses by the TPS was found to be 0.7% and differed by 0.6%, 0.7%, and 1.3% from the alanine, film and local ionisation chamber measurements respectively. Conclusions: Results obtained with the silica beads agree well with those obtained from conventional detectors including alanine, film and ionisation chambers. This together with the waterproof and inert characteristics and minimal dose fading associated with silica bead TLDs confirm their potential as a postal dosimetry audit tool in both water and plastic phantoms which could withstand challenges of temperature and humidity variation, as well as postal service delays. Highlights: Silica beads have been used as novel micro-TLDs in a national dosimetry audit across UK. The performance of the TLDs assessed in non-equilibrium conditions near tissue/lung interfaces. TLDs' Results agreed well with those obtained from alanine, film and ionisation chamber detectors.